1993
DOI: 10.1063/1.109567
|View full text |Cite|
|
Sign up to set email alerts
|

Investigation of optical limiting in C60 solution

Abstract: Results of experimental and theoretical investigation of optical limiting for 30 ns pulses at 527 nm in C60 are presented which suggest that apart from higher excited state absorption, other nonlinear processes may have an important role in the experimentally observed limiting action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(23 citation statements)
references
References 11 publications
0
22
1
Order By: Relevance
“…[15][16][17][18][19][20][21][22] Comparable optical limiting was reported for thick layers ͑each several millimeters thick͒ of C 60 in polymethyl methacrylate when pumped on resonance at 532 nm. 23 This research was supported by the U. S. Air Force Office of Scientific Research under AFOSR93-1-0191 ͑Dr.…”
Section: Di/dzϭϫ␣iϫni ͑2͒mentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22] Comparable optical limiting was reported for thick layers ͑each several millimeters thick͒ of C 60 in polymethyl methacrylate when pumped on resonance at 532 nm. 23 This research was supported by the U. S. Air Force Office of Scientific Research under AFOSR93-1-0191 ͑Dr.…”
Section: Di/dzϭϫ␣iϫni ͑2͒mentioning
confidence: 99%
“…16 The discovery of optical limiting in fullerenes evoked considerable attention because of its comparatively lower threshold limiting fluence. 14,18,19 Joshi et al 20 have found that their transmission measurements on C 60 deviates substantially from the kinetic model based on large excited state absorption ͑ESA͒ and they have attributed the discrepancy to the possibility of multiphoton absorption and/or nonlinear scattering along with ESA.…”
Section: Introductionmentioning
confidence: 96%
“…Besides, during the last decade, it was observed that fullerenes C 60 and C 70 present extensive delocalization of their three-dimensional π-electron conjugated systems [6][7][8] . For this reason it is expected that both C 60 and C 70 compounds show large third order optical nonlinearities; indeed, nonlinear refraction and absorption of C 60 and C 70 based solutions have been widely studied in recent years due to their potential applications in optical limiting, all optical switching and optical bistability processes [9][10][11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%